Reformasi Hukum Keluarga dan Perlindungan Hak Konstitusional dalam Putusan Mahkamah Konstitusi Indonesia - Robby Awaluddin Jamil (International Forum of Researchers and Lecturers, 2026)
The reform of family law in Indonesia represents an essential response to social developments and the growing demand for constitutional protection of citizens’ rights. Family law, primarily governed by Law Number 1 of 1974 on Marriage, has long been criticized for not fully reflecting substantive justice, particularly for vulnerable groups such as children born outside marriage, persons with mental disabilities, and couples facing complex marital relations. In this context, the Constitutional Court of Indonesia (Mahkamah Konstitusi) plays a crucial role as the guardian of the Constitution by promoting progressive reforms through its landmark decisions. This study examines the implications of five significant Constitutional Court rulings: Decision No. 46/PUU-VIII/2010 concerning the legal recognition of children born out of wedlock; Decision No. 93/PUU-XX/2022 addressing guardianship and the rights of persons with mental disabilities; Decision No. 69/PUU-XIII/2015 allowing post-nuptial agreements; and Decisions No. 68/PUU-XII/2014 and No. 24/PUU-XX/2022 regarding interfaith marriage. These rulings demonstrate a paradigm shift from a rigid legalistic approach toward a constitutional framework grounded in human rights, equality, and substantive justice. Furthermore, notaries hold a strategic position as public officials authorized to draft authentic deeds, serving as a bridge between constitutional values and legal practice. Notaries are not merely administrative actors but are responsible for ensuring that legal documents align with positive law and provide legal certainty and protection for individuals. Therefore, the reform of Indonesian family law should not remain solely at the normative level of Constitutional Court rulings but must be effectively implemented in daily legal practice.